Eradicating and eliminating infectious diseases: Past, Present and Future - Jai P Narain (Wolters Kluwer Medknow Publications, 2011)
During the past 60 years, a number of infectious diseases have been targeted for eradication or elimination, with mixed results. While smallpox is the only one successfully eradicated so far, campaigns on yaws and malaria brought about a dramatic reduction in the incidence in the beginning of the campaign but ultimately could not achieve the desired goal. There is again a renewed interest in disease eradication. The World Health assembly in May 2010 passed a resolution calling for eradication of measles by 2015; the target of polio eradication still remains elusive. In view of these developments, it is appropriate time to revisit the concept of disease eradication and elimination, the achievements and failures of past eradication programmes and reasons thereof, and possibly apply these lessons while planning for the future activities. This paper based on the Dr. A.L.Saha Memorial Oration describes various infectious diseases that have been targeted for eradication or elimination since 1950s, the potential direct and indirect benefits from disease eradication, and the issues and opportunities for the future.